2016
DOI: 10.1177/0271678x16666551
|View full text |Cite
|
Sign up to set email alerts
|

Colony stimulating factor 1 receptor inhibition eliminates microglia and attenuates brain injury after intracerebral hemorrhage

Abstract: Microglia are the first responders to intracerebral hemorrhage, but their precise role in intracerebral hemorrhage remains to be defined. Microglia are the only type of brain cells expressing the colony-stimulating factor 1 receptor, a key regulator for myeloid lineage cells. Here, we determined the effects of a colony-stimulating factor 1 receptor inhibitor (PLX3397) on microglia and the outcome in the context of experimental mouse intracerebral hemorrhage. We show that PLX3397 effectively depleted microglia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 54 publications
3
115
0
Order By: Relevance
“…Brain ischemia activates microglia that can damage neural structure or facilitate neural repair, depending on timing and context (52)(53)(54)(55). Microglia express IL-15 receptors and thus could be receptive to astrocytic IL-15.…”
Section: Discussionmentioning
confidence: 99%
“…Brain ischemia activates microglia that can damage neural structure or facilitate neural repair, depending on timing and context (52)(53)(54)(55). Microglia express IL-15 receptors and thus could be receptive to astrocytic IL-15.…”
Section: Discussionmentioning
confidence: 99%
“…Since many large motoneurons with high-level CSF1 expression were encircled by microglia in the spinal cords from both acute and chronic EAE mice, we presume that neuronal loss may be partly due to the action of microglia. However, Li et al (2017) reported that eliminating microglia with PLX3397 attenuated brain injury after intracerebral hemorrhage. Luo et al showed that administration of CSF1 or IL34 prevented the loss of pyramidal neurons and microgliosis in mouse hippocampus after kainic acid injection (Luo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In support of the hypothesis, microglial depletion has thus led to a broad range of positive and neuroprotective outcomes in distinct disease conditions by reducing neuroinflammation (Table ): ameliorating EAE (Heppner et al, ; Lassmann & Bradl, ; Nissen, Thompson, West, & Tsirka, ); enhancing remyelination in the cuprizone demyelination model (Beckmann et al, ); attenuating neurological abnormalities and brain edema in two stroke mouse models (Li, Li, et al, ); reducing mRNA levels of proinflammatory cytokines such as IL‐1β and TNF‐α induced by peripheral lipopolysaccharide injection after microglial depletion (Xie et al, ); or acute binge ethanol withdrawal with little negative effects on behavioral functions (Walter & Crews, ). In one of our previous studies, we have indicated that cranial irradiation can cause transient accumulation of microglial cells followed by persistent inflammation and pronounced expression of IL‐1β and CCL2 in the hippocampus (Han et al, ).…”
Section: Depleting Microglia In Diseases: the Friend In Need May Not mentioning
confidence: 94%